Soil carbon dioxide and methane fluxes from forests and other land use types in an African tropical montane region - Wanyama, Ibrahim; Pelster, David E.; Butterbach-Bahl, Klaus; Verchot, Louis V.; Martius, C.; Rufino, Mariana C. (Springer, 2019)
In the last 40 years, large areas of the Mau forest, the largest contiguous tropical montane forest in East Africa, have been cleared for agriculture. To date, there are no empirical data on how this land use change affects carbon dioxide (CO2) fluxes from soil respiration and soil methane (CH4) fluxes. This study reports measured annual soil CO2 and CH4 fluxes from the native Mau forest and previously forested lands converted to smallholder grazing land, smallholder and commercial tea plantations and eucalyptus plan- tations. Fluxes were measured weekly from August 2015 to August 2016 using the static chamber method. Grazing lands had the highest (p = 0.028) cumulative respiratory CO2 fluxes (25.6 ± 2.9 Mg CO2–C ha-1 year-1), whereas lowest fluxes were observed in commercial tea plantations (5.6 ± 0.5 Mg CO2–C ha-1 year-1). Soil respiratory CO2 fluxes were positively correlated with soil pH, but negatively correlated with soil C:N ratio. Annual soil fluxes were explained by soil pH, bulk density and the interaction between soil pH and C:N ratio. Most soils were sinks for atmospheric CH4 across all land use types. Methane uptake was highest for native forest sites (- 3.08 ± 0.35 to - 5.84 ± 0.61 kg CH4–C ha-1 year-1) and for eucalyptus plantations (- 3.43 ± 0.19 kg CH4–C ha-1 year-1). Uptake decreased significantly with increasing land use intensity (smallholder tea plantations: - 1.42 ± 0.09 kg CH4–C ha-1 year-1, commercial tea plantations: - 1.44 ± 0.29 kg CH4–C ha-1 year-1). Soils of smallholder grazing lands had the lowest CH4 uptake rates (- 0.36 ± 0.25 kg CH4–C ha-1 year-1). Annual CH4 uptake was negatively correlated with mean annual soil water-filled pore space (p \ 0.01) and bulk density (p = 0.003) and decreased with increasing soil inorganic NH4? concentrations (p = 0.03). Annual soil CH4 can be explained by mainly soil water content and bulk density and these factors are related to gas diffusion. Our study shows that converting tropical montane forests to managed land use types affects soil CO2 and CH4 fluxes. Specifically, the CH4 sink strength in managed land use types of these montane tropical soils was reduced to less than half of the sink strength in the native forest. Soil respiratory CO2 fluxes were also altered by land use with grazing lands emitting 3–4 times more CO2 than the other land use types.